Comparison of Maximum Phonation Duration and S/Z Ratio in Individuals with Asthma, Tuberculosis and Clinically Normal Voice - Shrestha, Susmita; Adhikari, Anil Kumar (Medical Journal of Shree Birendra Hospital, 2019)
Introduction: The ability of a person to phonate a sound gets affected in different laryngeal and respiratory pathology which can be measured by the help of two measure called as Maximum Phonation Duration (MPD) and S/Z ratio that helps to assess the efficiency of respiratory and phonatory system. The aim of this study is to measure the MPD and S/Z ratio in Normal, Tuberculosis and Asthma group patient. Methods: The participant included Normal, Asthma and Tuberculosis patient where the recording was made in a quiet room with the help of PRAAT software and the participant were asked to sustain phonation of sound on single breath. Analysis was done with helps of SPSS version 25.0. Results: There was a significant difference noted in MPD of /a/, /i/, /u/ sound between control and experimental group. MPD were significantly shorter in Asthma and Tuberculosis group compared to Normal group with no significant difference in S/Z ratio. Conclusions: Maximum Phonation Duration is more reduced in Asthma and Tuberculosis patient compared to Normal group which indicate Asthma and Tuberculosis patient has to put more effort to phonate a sound.